The Effect of Activities Congruent with Brain Based Learning Model on Students' Mathematical Achievement - Erol, Mustafa; Karaduman, Gulsah Batdal (ANKA PUBLISHER, 2018)
The purpose of this study is to investigate the effects of teaching activities prepared with brain based learning model on mathematics success of primary school students. In the study, pre-test-post-test and permanence test half-experimental design with control group was used. The participants of the experiment consist of total 91 fourth-grade primary school student's continuing education in Istanbul, and also taking part in experimental and control groups. Data were collected by using Personal Information Form prepared by the researchers and Mathematics Achievement Test About the Subject of Natural Numbers in the Fourth Grade also developed by the researchers. To analyze data, it was used for SPSS package program. According to the findings of the research, a significant difference has been found in favor of the experimental group regarding mathematics achievement of the fourth grade students and persistence of knowledge they have learned.
Keywords: Brain-Based Learning; Mathematics Lesson; Academic Achievement; Neurosciences & Neurology